Evaporative drying from hydrophilic and hydrophobic single pores and porous media - Chakraborty, Partha Pratim (Kansas State University, 2022)
Reduction of water usage is a challenging issue in food-energy-water nexus; approximately two-thirds of the global water withdrawals are responsible for food production, and water withdrawals are predicted to increase in the future to produce more food to meet the demands of a growing global population, projected to reach 9.8 billion by 2050. Arid or semi-arid areas are facing increasing pressure for water resources, yet irrigation is critical for increasing yields; 20% of global land is irrigated, but it accounts for 40% of crop production [1]. One approach to conserving soil moisture is to restrict evaporation by altering soil wettability. Any material can be classified into two categories of wettability: hydrophilic (i.e., water loving) and hydrophobic (i.e., water repelling), and the wettability is measured using the contact angle (i.e., the angle formed by the liquid at the solid-liquid-vapor interface) of liquid droplets. For hydrophilic surfaces, the contact angle is less than 90°, and for hydrophobic surfaces, it is greater than 90°. Wettability impacts evaporation; previous studies indicated that inclusion of hydrophobicity can reduce evaporation rates by 50-65% in a porous media. In this dissertation, the impacts of wettability on evaporation of water from porous media were investigated from single pores and porous media. The evaporation phenomena were studied from simulated soil pores created with three hydrophilic glass 2.38-mm-diameter spheres or three hydrophobic 2.38-mm-diameter spheres. Water droplets (i.e., 4-µL) were evaporated from the pore in three different experiments. Experimental conditions were varied, including air temperatures (i.e., 20-22.2° C), relative humidities (RH) (i.e., 30%, 45%, 60%, and 75% RH), and single pore geometries [i.e., center-to-center distances of the spheres (i.e., 2.7 mm, 2.8 mm, 3.13 mm)]. The relative humidity played a role in droplet evaporation, as evaporation rates were slower at higher RH. For all cases, the wettability impacted the droplet evaporation. At each relative humidity level set for experiments (i.e., 30%, 45%, 60% and 75%), the evaporation rates were 1.11-1.47 times higher for hydrophilic pores than hydrophobic pores. The pore size also affected the evaporation phenomena, as the evaporation rates were 1.23-1.3 times higher for larger pore sizes (e.g., center-to-center distances of 3.13 mm compared to 2.7, 2.8 mm) at 20°C, 60% RH. Evaporation from single pores was observed using a high-speed camera. Wettability impacted the contact line movement, including pinning (i.e., solid-liquid-vapor contact lines do not move) and depinning (i.e., solid-liquid-vapor contact lines move). In glass pores comprised of three spheres, the solid-liquid-vapor contact line on one sphere was pinned and the contact line depinned on the remaining two spheres, resulting in contact line motion. In Teflon pores comprised of three spheres, all solid-liquid-vapor contact lines on each of the three spheres decreased with time. During evaporation, the whole droplet eventually ruptured and created a liquid island between two of the three spheres. Liquid islands formed between two spheres and in an isothermal condition both radii of curvature of the liquid islands decreased in size due to evaporation. Subsequently, evaporation from simulated soil columns was investigated to understand evaporation dynamics and evaporation stages in multi-layered porous media. In a typical porous media, three different evaporation stages are found: constant rate period, falling rate period and subsequent slower rate period. In the constant rate period, the porous media remains saturated, and water is evaporated from the surface by means of natural or forced convection maintaining a constant rate. The constant rate continues until the water can move to the top surface by action of capillary force. The depth of drying front at the end of constant rate is marked as the characteristic length which is defined as the maximum hydraulically connected region from the evaporative front to the top surface. When this hydraulic connection breaks down, the evaporation rate experiences a sharp decrease, defined as the falling rate period, where liquid islands are formed throughout the porous section. When the liquid islands rupture, the evaporation rate further reduces; this is defined as the slower rate period of evaporation. For multi-layered porous media, two different columns (i.e., hydrophilic and hydrophobic) were prepared. Approximately 1320 glass or Teflon 2.38-mm-diameter spheres were filled in 6-cm-height, 1.88-cm-diameter glass beakers. During these experiments, a heat flux of 1000 W/m² was applied using a solar simulator and 5 mL of water out of a total of 5.8 mL was evaporated. Experiments were conducted for seven days, and each experiment was replicated five times. The evaporative mass loss was recorded with a sensitive scale (± 0.01 g) and the evaporation rates were measured at 22.2°C, 60% RH. The initial evaporation rate was 1.5 times higher in hydrophilic column (e.g., 7.5 mm/day) than the hydrophobic column (e.g., 5 mm/day). In the experiments with hydrophilic or hydrophobic porous columns, different evaporation stages were analyzed. Due to homogeneity of the porous column, the constant rate period of evaporation was insignificant for both glass and Teflon spheres. From the very beginning, the evaporation experienced a sharp decrease (i.e., the falling rate period) and, subsequently, the slower period of evaporation for both glass and Teflon samples. The evaporative mass loss was greater in glass (i.e., 3 g) sample than the Teflon (i.e., 2.4 g) after seven days of experiment, indicating higher evaporation rate from hydrophilic porous media. The drying front, the distance from the unsaturated part to the saturated portion of the porous media, was visualized and captured with a high-resolution x-ray from the third day until seventh day of evaporation. The drying front propagated faster in glass sample than Teflon...
Keywords: Evaporation; Porous media; Wettability; Liquid island; Single pore